Chalet and resort guests expectation and perception of the quality factors using SERVQUAL dimension - Omar, Muhd Khaizer; Shamsul Azman, Nur Arnie Sazerin; Jusoh, Rosnani; Jamaluddin, Rahimah; Abdul Kadir, Suhaida (Ubiquity Press, 2020)
This article propagates the guests feedback on tourism experience based on the three major quality factors: service, facility, and location. We employ a descriptive quantitative survey and utilize five dimensions of SERVQUAL to determine guests expectation and perception from lodging experience offered by the chalet and resort entrepreneurs along the beach coast of Pengkalan Balak, Malacca, Malaysia. A total of 152 tourists who stay at five selected chalets and resorts are selected using a random sampling technique for the sample of the study. The results of the analysis indicate that the guest expectation on the service quality, the facility, and the environment is higher compared to guest actual experience during their stay in the designated premises. It is evident that the customer satisfaction level is low and the lodging providers are advised to take proactive measures in ensuring the quality of the service, the facility and the convenience of the location are at the global standard. It is important to note that the findings do not generalize to other lodging facilities, for example, hotel and homestay services. The findings from this study projects and assists chalet and resort entrepreneurs to advocate salient improvement for quality standards which ultimately flourish customer satisfaction level and discern best strategies in promoting the beach coast of Pengkalan Balak to be one of the best coastlines and finest chosen tourism destination in Malaysia.